Formative Assessment in MBA Education: A Case Study from Nepal - Pudasaini, Sanjay (Journal of Innovation in Academia, 2025)
This study employs a mixed-methods approach to investigate the integration and impact of formative assessments in MBA programs across Nepal. Using stratified purposive sampling, 211 faculty members from 28 institutions under six universities participated. Quantitative findings reveal that while formative assessments are incorporated into curricula, their implementation varies widely. Faculty generally hold neutral views on their effectiveness, with more experienced educators being more positive. These assessments are associated with improved competencies in decision-making, critical thinking, and leadership. Qualitative findings highlight innovative practices like reflective journals, case studies, and collaborative projects that support student learning. However, challenges such as limited institutional support, insufficient digital infrastructure, and a lack of faculty training hinder optimal implementation. The study emphasizes the transformative potential of formative assessments and recommends policy reforms, professional development, and enhanced technology. Its integration of theory and practice offers a model for similar contexts globally.